Balanced Investment Treaties and the BRICS. (27th August 2018) - Cai, Congyan
Abstract : Brazil, Russia, India, China, and South Africa (the BRICS) have emerged as a new hub of power in international relations. They have begun to speak out jointly on a wide range of issues and to explore cooperating collectively. For instance, they strongly urge the Bretton Woods institutions to address their legitimacy deficits by transferring substantial voting power to emerging powers, and suggest that failure to do so will "run the risk of seeing [those institutions] fade into obsolescence." The investment treaty regime may be another field in which they can exert influence, but the investment treaty policies of BRICS countries are diverging now more than ever. In particular, India and South Africa have taken significant measures, such as terminating investment treaties, that cast doubt on whether the BRICS can play a collective role in reforming such treaties. In this essay, I make two arguments. First, the recent investment treaty policies of some BRICS (India, South Africa, and to some extent Brazil) have shifted from one imbalanced approach that is too protective of foreign investors to another that is too protective of host states and is likely to be rejected by major powers such as the European Union, the United States, and China. Second, the BRICS together have the ability to craft approaches to investment treaties that encourage greater balance in the regime overall, including by remedying some of the defects inherent in the traditional investment treaties.